1988
DOI: 10.1107/s0021889887010434
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer roughness evaluated by X-ray reflectivity

Abstract: A crystal diffraction theory has been developed and compared with experimental measurements in order to model the integrated reflectivity of multilayer structures. This study shows that the most important defect reducing the integrated reflectivities of the multilayer structures studied was correlated roughness (root mean square value about 7 A). The theory describes correlated roughness as a probability distribution of the substrate surface displacement. A computer simulation and an analytical solution have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Brown, called XTALR.COM exists, ref. [3], which in its preliminary stages finds f in just the manner described abovei.e. by using Henke's numbers when available, and computing them according to Cromer when not.…”
Section: Apnendix 4 Two Expressions For the Reflectivity Suitable Fomentioning
confidence: 86%
See 1 more Smart Citation
“…Brown, called XTALR.COM exists, ref. [3], which in its preliminary stages finds f in just the manner described abovei.e. by using Henke's numbers when available, and computing them according to Cromer when not.…”
Section: Apnendix 4 Two Expressions For the Reflectivity Suitable Fomentioning
confidence: 86%
“…[5], [61, [7] ). Rather, what is done here is the development of a formalism and a computer program conveniently applicable to a problem of continuing interest at the Naval Research Laboratory [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this equal probability or sawtooth-like distribution is a reasonable approximation for the roughness for some cases. 3 In particular, this strategy is expected to give good results for higher order diffraction. Calculations were performed for various thicknesses of the intermediate layer.…”
Section: Theoretical Methodsmentioning
confidence: 98%